The Determinants of Labor Force Participation of Women in Turkey: A Binary Logit Analysis - Varol, Fatih (Journal of History Culture and Art Research, 2017)
Compared to many developed and developing countries, the labor force participation of women in Turkey is very low. More interestingly, the rate of the labor force participation of women had declined from the 1980s to 2008 although it had increased in many countries. This paper examines the major determinants of the labor force participation of women in Turkey by using binary logit model on the World Values Survey of 2007. It finds that high level of education, high level of income, and being chief wage earner in the household have a positive impact on the labor force participation of women in Turkey. While the ageing of women has a positive impact until the age of mid-30s, its effect is negative after the age of mid-30s. Marriage and the increasing number of children have also negative impacts on the labor force participation women.